PERKEBUNAN TEMBAKAU DAN KAPITALISASI EKONOMI SUMATERA TIMUR - Akbar, Allan (Puslitjakdikbud Balitbang Kemdikbud, 2016)
AbstractEast Sumatra area was formerly a wilderness, in a short time, has become the mostprofitable plantation area in Sumatra. This development took place due to the success oftobacco cultivation in East Sumatra. The big profit of this tobacco plantation has attractedthe interest of foreign investors to invest in East Sumatra. Besides generated great wealth,tobacco plantation has also brought some impacts on the development of East Sumatra.This study will highlight how the development of tobacco plantations brought wealthto East Sumatra as well as the impacts that occured from the widespread of the newplantings. Using the historical methods, this research aims to explain the economicchanges that occurred in East Sumatra, especially since the rise of the opening of thetobacco plantations by foreign investors. From this study, it appears that the openingof the tobacco plantations has affected to four important changes, which are changes inlifestyle of the traditional elite, the forming of social gap, changes in the demographiccomposition, and the emergence of new towns. AbstrakDaerah Sumatera Timur yang sebelumnya merupakan hutan belantara, dalam waktusingkat telah menjadi wilayah perkebunan paling menguntungkan di Pulau Sumatera.Perkembangan ini terjadi berkat keberhasilan budidaya tembakau di Sumatera Timur.Keuntungan yang besar dari perkebunan tembakau menarik minat para investor asinguntuk menanamkan modalnya di Sumatera Timur. Selain mendatangkan kekayaan yangbesar, perkebunan tembakau telah membawa beberapa dampak bagi perkembanganSumatera Timur. Penelitian ini akan menyoroti bagaimana perkembangan perkebunantembakau hingga mendatangkan kekayaan bagi Sumatera Timur serta dampak apa sajayang ditimbulkan akibat dari maraknya pembukaan perkebunan tersebut. Menggunakanmetode sejarah, penelitian ini bertujuan untuk menjelaskan perubahan ekonomi yangterjadi di Sumatera Timur terutama sejak maraknya pembukaan perkebunan-perkebunantembakau oleh para investor asing. Dari penelitian ini terlihat bahwa pembukaanperkebunan tembakau berdampak pada empat perubahan penting, seperti perubahan gayahidup kalangan elite tradisional, terjadinya jurang sosial, perubahan komposisi demografi,dan munculnya kota-kota baru.